2018
DOI: 10.1515/med-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer-Specific of DD3-driven oncolytic virus-harboring mK5 gene

Abstract: AbstractProstate cancer (PCa) is the second most diagnosed cancer in Western male population. In this study, we insert mK5 (the mutational kringle5 of human plasminogen) into a DD3-promoted (differential display code 3) oncolytic adenovirus to construct OncoAd.mK5.DD3. E1A.dE1B, briefly, OAd.DD3.mK5. DD3 is one of the most prostate cancer specific promoters which can transcriptionally control adenoviral replication. mK5 has been proved to be able to inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Ad vector based on PB promoter may target AR positive PCa 41 . Hao et al designed OncoAd.mK5.DD3 vector that effectively inhibited PCa 42 .…”
Section: Virus Vaccinementioning
confidence: 99%
“…Ad vector based on PB promoter may target AR positive PCa 41 . Hao et al designed OncoAd.mK5.DD3 vector that effectively inhibited PCa 42 .…”
Section: Virus Vaccinementioning
confidence: 99%
“…Prostate cancer gene 3 (PCA3/DD3) is a PCaspecific marker identified recently. Hao et al [36] designed OncoAd.mK5.DD3 vector to drive the expression of mK5 (the mutational kringle5 of human plasminogen) by DD3 promoter specially in PCa cells and the results showed that OncoAd.mK5.DD3 was able to inhibit PCa efficiently. Taking advantages of the sensitivity and specificity of DD3 as PCa marker, a test kit Progensa™ (Gen-Probe Inc. San Diego, CA, USA) was developed for the detection of PCa cells in urine [37].…”
Section: Prostate-specific Promotermentioning
confidence: 99%
“…Additionally, mK5 has a stronger effect on the induction of HUVECs apoptosis [13]. Previous studies have shown that OV-mediated mK5 can inhibit the growth of colorectal cancer [14] and prostate cancer [15]. Cancer often involves changes in the growth and proliferation of cells.…”
Section: Introductionmentioning
confidence: 99%